QUALITY EVALUATION SYSTEM INDICATORS OF TRANSPORT SERVICES IN RAILWAY FREIGHT TRANSPORTATION (Transport systems and technologies, 2018)
A technical and economic methods of calculation and estimation of the transport ser-vices quality parameters are given. They allow to set conditions for obtaining the desired operational, technical and commercial characteristics of the transport of goods in differ-ent kinds of combinations with rational use of the rolling stock based on an assessment of user requirements to the rail transport service of Ukraine.
Keywords: the quality of transport services, rail services, types of connections, turnover of the car, goods delivery by rail, linear programming.